2020
DOI: 10.18502/ijph.v49i5.3212
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Public Preferences for Changes in the Health Insurance Benefit Package Policies in Iran: A Survey Approach

Abstract: Background: This study aimed to identify the public preference in health services, the principles that Iranian people consider important, and the aspects of trade-offs between different values in resource allocation practices. Methods: This quantitative study was conducted to investigate public preferences on Health Insurance Benefit Package (HIBP) in 2017. A structured questionnaire was used for data collection, including the preferences of the people who live in Tehran, were above 18 year, and were covered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Among the selected studies, eighteen identified social values through the use of expert opinions (7;12;18;19;21–34). One study identified social values merely by analyzing policy documents and national evidence (12), while two studies involved a public survey to elicit social values (34;35). Three studies used multiple sources to identify values (12;28;34), two of which combined policy documents with expert opinions (12;28), and the remaining study used both experts and public opinions (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the selected studies, eighteen identified social values through the use of expert opinions (7;12;18;19;21–34). One study identified social values merely by analyzing policy documents and national evidence (12), while two studies involved a public survey to elicit social values (34;35). Three studies used multiple sources to identify values (12;28;34), two of which combined policy documents with expert opinions (12;28), and the remaining study used both experts and public opinions (34).…”
Section: Resultsmentioning
confidence: 99%
“…Although policy-related process criteria were extracted from only a relatively small number of the selected studies, such criteria can substantially enhance the legitimacy of the value assessment framework. According to surveys, ignoring the transparency of the service prioritization process, and making decisions without involving relevant stakeholders, including citizens, constitutes an obstacle and may impede the achievement of universal health coverage in Iran (35;40). The studies included in the review used three sources for the identification of relevant decision criteria and social values, that is, policy documents, expert opinions, and general public/patient opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, such decisions have been taken based on the bargaining power of various parties attending the ISCHI’s meetings. For instance, the insurance corporations mainly take into account the financial burden of services [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, such decisions have been taken based on the bargaining power of various parties attending the ISCHI's meetings. For instance, the insurance corporations mainly take into account the nancial burden of services (10,11).…”
Section: Introductionmentioning
confidence: 99%